2015
DOI: 10.20870/oeno-one.2015.49.2.88
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traditional and light pruning on viticultural and oenological performance of Bobal and Tempranillo vineyards

Abstract: <p style="text-align: justify;"><strong>Aim</strong>: Light pruning may improve vine yield and quality although vineyard responses are variable. We assessed the effects of traditional manual pruning and mechanical light pruning on the viticultural and oenological performance of <em>Vitis vinifera </em>cv. Bobal and cv. Tempranillo.</p><p style="text-align: justify;"><strong>Methods and results</strong>: During 2008-2011, Bobal and Tempranillo vineyards unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…Some physical-chemical characteristics of grapes (Tables 1 and 2) were affected by the three factors in the study. Overall, TSS was negatively affected by MEC in all three years, as observed by other authors (Reynolds, 1988;Clingeleffer and Krake, 1992;Bovio and Lisa, 1996;Pérez-Bermúdez et al, 2015). However, there was a correlation between the TSS decrease and the yield increase induced by MEC, particularly as the organic amendments (namely Manure, MSWC and Sludge) provided more principal macronutrients, particularly N, and increased total dry mass production (Figure 1) (Botelho et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some physical-chemical characteristics of grapes (Tables 1 and 2) were affected by the three factors in the study. Overall, TSS was negatively affected by MEC in all three years, as observed by other authors (Reynolds, 1988;Clingeleffer and Krake, 1992;Bovio and Lisa, 1996;Pérez-Bermúdez et al, 2015). However, there was a correlation between the TSS decrease and the yield increase induced by MEC, particularly as the organic amendments (namely Manure, MSWC and Sludge) provided more principal macronutrients, particularly N, and increased total dry mass production (Figure 1) (Botelho et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…Although the TSS in grapes was reduced by the increase in yield, the total sugar production (data not shown) increased in the treatments with higher yield, as also observed by Pérez-Bermúdez et al (2015). In addition to the reduction in TSS caused by the increase in productivity, there was a significant tendency for Sludge grapes to have lower TSS when compared to the other organic amendments, including those with similar yields.…”
Section: Discussionmentioning
confidence: 56%
“…The basic chemistry (ºBrix, pH, color, titratable acidity and polyphenol index) for each grape sample was determined by Fourier-transform infrared spectrometry. For more analytical details, see Pérez-Bermúdez et al (2015).…”
Section: Grape Characterizationmentioning
confidence: 99%
“…Our results are in line with those reported by Main and Morris (2008) for Cynthiana grapevines, who observed that pruning had a slight influence on this cultivar since the authors found only minor differences in vine nutrition and fruit composition between the four pruning methods applied to the vineyard. Recently, we determined the effects of severe or light pruning on Bobal and Tempranillo vines by evaluating vine vigor and yield as well as grape and wine characteristics (Pérez-Bermúdez et al, 2015). In both vineyards with soil tillage, light-pruned vines produced more clusters, smaller berries and grape yield increased significantly (30%).…”
Section: Effect Of Cover Crops In Grapevine Inter-rows and Pruning Tementioning
confidence: 99%
See 1 more Smart Citation